Psychological impact of being wrongfully accused of criminal offences: A systematic literature review. (January 2021) - Brooks, Samantha K; Greenberg, Neil
Being wrongfully accused of criminal offences can lead to serious negative consequences to those wrongfully accused and their families. However, there is little research on the psychological and psychosocial impacts of wrongful accusations. We conducted a systematic literature review to collate the existing literature, searching four electronic literature databases and reference lists of relevant articles. Data were extracted from 20 relevant papers, and thematic analysis was conducted on the data. Eight main themes were identified: loss of identity; stigma; psychological and physical health; relationships with others; attitudes towards the justice system; impact on finances and employment; traumatic experiences in custody; and adjustment difficulties. The psychological consequences of wrongful accusations appear to affect the lives of those accused seriously, even after exoneration or overturning of convictions. Strategies for improving public perception of wrongful convictions should be explored, and specific mental-health systems should be established to support those who are wrongfully accused.